IMPROVING THE FIFTH-GRADE ELEMENTARY STUDENTS’ LEARNINGOUTCOMES IN INTEGRATED THEMATIC LEARNING ON THEME 6 USINGTIME TOKEN MODEL - Yolla Melisandy; Mai Sri Lena (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper is based on research about learning in which the students still obtain learning from the teachers only and the students did not contribute during the learning process mostly. It is because the teacher did not implement innovative, creative, and diverse models. The research aims to describe how Integrated Thematic learning assisted by Time Token modelin Class V at SDN 16 Enam Lingkung in Padang Pariaman can improve students’ learning outcomes. The research approach is Classroom Action Research. The research subjects involved 18 teachers and students in class V. Data collection was carried out through observations, documents, tests, and non-tests. The research was conducted in two phases, Cycle I and II. In Cycle I, according to the lesson plan's findings, the average percentage was 83.33% (excellent), conversely, in Cycle II, the average percentage was 94.44%. (excellent). In Cycle I, according to the teacher, the average percentage was 82.81% (good), conversely, in Cycle II, the average percentage was 93.75%. (excellent). Students' average learning outcomesin Cycle I were 75.9% and the student’s average learning outcomes in Cycle II were 89.13%. Thus, the Time Token technique in integrated thematic learning indicates students' learning outcomes produce an improvement